2018
DOI: 10.1002/lpor.201800027
|View full text |Cite
|
Sign up to set email alerts
|

Transporting the Optical Chirality through the Dynamical Barriers in Optical Microcavities

Abstract: In mixed phase space structures, the stable islands and chaotic sea are separated by dynamical barriers. Considering the small tunneling rate, intuitively, the properties of long‐lived resonances within stable islands are supposed to be less affected by the perturbations in chaotic sea. Here, the modifications on the chaotic sea which can be transported through dynamical barriers and strongly affect long‐lived resonances within stable islands are experimentally demonstrated. In waveguide‐connected quadruple mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Take the scattering of the cylindrical waves, for example. If the index modulation itself has an angular momentum M = 2 (e.g., a quadruple cavity with a uniform refractive index [31,32]), then a cylindrical wave of angular momentum m will be scattered strongly into the m ± 2 channels in general [33]. More specifically, the m = ±1 channels are scattered strongly into each other and the m = ±3 channels.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Take the scattering of the cylindrical waves, for example. If the index modulation itself has an angular momentum M = 2 (e.g., a quadruple cavity with a uniform refractive index [31,32]), then a cylindrical wave of angular momentum m will be scattered strongly into the m ± 2 channels in general [33]. More specifically, the m = ±1 channels are scattered strongly into each other and the m = ±3 channels.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…. 10 4 [19,50]. However, the modes in the microstar have the unique property that almost half of the mode's intensity |ψ| 2 is trapped outside of the cavity whereas WG modes only leak evanescently to the surrounding area of the cavity.…”
Section: -4mentioning
confidence: 99%
“…Figure 1(b) illustrates the interaction process between the waveguide and microcavity. Therefore, by defining the quantities L and WG as the complexvalued dimensionless frequencies of the left cavity modes and waveguide modes, the formation of chirality in the left-sided cavity can be qualitatively understood with the following 4 × 4 non-Hermitian Hamiltonian [17,32,33].…”
Section: A Coupling In Passive Systemmentioning
confidence: 99%
“…For this purpose, the rational way is to drive the microcavity to the status of chirality where the balanced weights of the CW or CCW component are broken. Thus far, several cate-gories of techniques to address the issue have been intensively studied and well developed [17][18][19][20]. For instance, Liu et al have demonstrated a unique and robust mechanism, which is assisted by chaotic-to-regular tunneling in dye-doped polymer microdisks with low refractive index, to realize the strong chirality in a deformed optical microcavity [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation